Sakral dan Profan dalam Perkembangan Ideologi Politik Agama - Jarman Arroisi (TSAQAFAH, 2017)
Mostly, a research about nation ideology is related to a religion. Some people wish the religion becomes foundation for their nation, but others expect the opposite. The first type is optimistic that the religion will be able to help the nation to create a life with justice, prosperity, honesty, respect, unity in diversity, morality, and other sacred values. Therefore, there is no bargaining for integrity between religion and politics. They think religion and politics must be integrated with no exception, including the religion and the politics in Indonesia. The founders of Indonesia had said that the nation has to pay most attention to Moslem people’s privileges as the majority of Indonesian people. Meanwhile, according to the second type, Islam doesn’t have to play its role formally for the nation. It is enough for the religion to affect people’s mindset and their action. By using critical-analysis method, this paper tries to observe how the real process of political thought history including its ideological construction and its theory works together in one side, and how Islamic political thought develops and changes step by step to be profane and secular in another side. Finally, it will be revealed that a nation with a religion as its foundation to manage its government guarantees security, justice, prosperity, welfare, and happiness. It is more promising than a nation which marginalizes religion in managing its national affairs. It is proven by the Islamic history how the Prophet Muhammad had managed Islamic government very well and successfully.